Influence of bonding compression and air gap on the acoustic absorption of spunbond–resinated felt composites - Hasan Basri; Dafit Feriyanto (Jurnal Polimesin, 2025)
Spunbond-resinated felt is a common composite material used for automotive purposes. Reducing vehicle noise requires lightweight, cost-effective sound-absorbing materials. This study focuses on researching more lightweight and low-cost materials through examining how bonding compression and an air gap affect the acoustic absorption of Spunbond–Resinated felt composites with varying grammage (800–1400 g/m²) and thickness (15–22 mm). The novelty of this research is in the use of lower grammage and the existence of an air gap compared with the existing product and previous study. Acoustic absorption tests were conducted using an impedance tube with air-gap depths of 0, 10, and 15 mm behind the samples. Additional tests were conducted on compressed samples, 50% of the original thickness, to observe the effect of increased density. Results show that felt with 1200 g/m² provides the best overall absorption. Thickness compression reduces absorption by approximately 13–23%, whereas the introduction of an air gap significantly enhances absorption, particularly for lower-grammage materials. Notably, an 800 g/m² felt combined with a 15 mm air gap outperformed a 1400 g/m² felt without an air gap. These findings demonstrate that appropriate grammage and air gap design can enhance sound absorption, enabling lighter materials such as 800–1000 g/m² felt to meet noise-reduction requirements.